Kayangan Jubin Sdn Bhd / Fa’ezah Mamat...[et al.] - Mamat, Fa’ezah; Abd. Razak, Suhaili; Salleh, Rohaya; Mohd Sabry, Nabilah; Yusof, Nor Yusnani (2007)
Kayangan Jubin Sdn Bhd is a company that supplies various types of tiles. We Supply the latest design in many types of size. We also provide delivery service. Tiles have a better prospect to be developed and they also have high commercial values for local and international market. This business operates in Jalan Jejawi, Kangar Perlis.